The Inuit - Cunningham, Kevin, 1966-; Benoit, Peter, 1955- (New York : Children's Press, 2011)
An exploration of the Inuit, discussing their history, dress, survival skills, society, and more.
Presents an introduction to the Inuit peoples.
Includes bibliographical references (p. 44-45) and index.
Keywords: Inuit -- Juvenile literature; Eskimos -- Juvenile literature; Inuit; Eskimos; Inuit